International Management / A Review of Strategies and Operations: Third Edition - Brooke Michael Z (Stanley Thornes (Publishers) Ltd, 1996)
This book provides an ideal introduction to the key issues faced by international managers. Acknowledgements, Preface, International Management, Trade and Investment, Corporate Strategy, Trade in Goods and Services, Trade in Knowledge and Expertise, Foreign Investment, International Marketing Management, International Financial Management, Personnel and Industrial Relations, Decision-Making and Organization, International Corporate Planning, The Economic Environment, National Differences, The Company and the Nation State, International Organizations, International Management: The Future, Notes, Bibliography, Index.